2011
DOI: 10.1111/j.1752-4598.2011.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wild ungulate grazing on Orthoptera abundance and diversity in subalpine grasslands

Abstract: 1. Grasslands cover approximately 40% of the Earth's terrestrial landscape, supporting large communities of vertebrate and invertebrate herbivores. Orthoptera play an important role, consuming relatively large amounts of biomass. Their occurrence can be strongly affected by habitat diversity and structure, which can be shaped by large herbivores. Several studies have focused on the impact of livestock on Orthoptera communities, but little is known about how wild ungulates influence the abundance and diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…Conversely, the positive relationship of another group of herbivores-grasshoppers-to grazing is consistent with other grazing studies in these meadows (Holmquist et al 2010;2013) and elsewhere (Bock et al 2006;Cease et al 2012;Fartmann et al 2012). Although vertebrate grazers are herbivorous competitors, many grasshoppers prefer grazed areas with a) reduced canopy and litter, and b) increased bare ground, because access to bare ground facilitates soil oviposition, and the warmer ground resulting from reductions in cover likely speeds development (Huntly and Inouye 1988;Fartmann et al 2012; but see Spalinger et al 2011). …”
Section: Discussionsupporting
confidence: 71%
“…Conversely, the positive relationship of another group of herbivores-grasshoppers-to grazing is consistent with other grazing studies in these meadows (Holmquist et al 2010;2013) and elsewhere (Bock et al 2006;Cease et al 2012;Fartmann et al 2012). Although vertebrate grazers are herbivorous competitors, many grasshoppers prefer grazed areas with a) reduced canopy and litter, and b) increased bare ground, because access to bare ground facilitates soil oviposition, and the warmer ground resulting from reductions in cover likely speeds development (Huntly and Inouye 1988;Fartmann et al 2012; but see Spalinger et al 2011). …”
Section: Discussionsupporting
confidence: 71%
“…It is known that these invertebrates only consume 20-30% of the plant biomass removed (Bailey andRiegert 1973, Ingrisch andKo¨hler 1998), while the rest is ''dropped'' to the ground and is directly entering the soil food-web. In addition, Belovsky and Slade (2000) showed that increasing grasshopper densities lead to increases in soil N cycling, and Spalinger et al (2012) found increased grasshopper abundance with increasing FIG. 2.…”
Section: Aboveground Vertebrate and Invertebrate Herbivore Impact On mentioning
confidence: 99%
“…This indicates that butterflies are well conserved in both types of ENs sampled here. The response of grasshoppers to the presence of wild grazers here is more surprising, as other studies in Europe and Africa have shown that they are not much influenced by the type of grazer [32,33]. This is most likely due to a greater variety in the types of grazing in the wild grazed area, creating more niche opportunities, or this might be due to differential grazer intensities between the two ENs [17].…”
Section: Discussionmentioning
confidence: 62%
“…and so need grazing to maintain their diversity and function within grasslands [30,31]. Yet, grasshopper diversity seems to show little change when livestock grazing is compared to that of wild ungulates [32,33], with the disturbances caused by livestock grazing seemingly mimicking those of wild ungulate grazing. Butterflies on the other hand are more sensitive to the presence of grazers in general [3].…”
Section: Introductionmentioning
confidence: 99%